Effect of emodin on c-myc proto-oncongen expression in cultured rat mesangial cells. - Liu Zhi-Hong; Li Lei-Shi; Hu Wei-Xin; Zhou Hong (Acta Pharmacologica Sinica, 2016)
"AIM: To explore the possible molecular mechanism of emodin on the inhibition of glomerular mesangial cells (MC). METHODS: In rat MC culture, c-myc mRNA level was detected by dot-blotting as expressed by the dilutions of the total RNA on the visible dots. RESULTS: Low level c-myc mRNA was found in serum-free cultured quiescent MC. Addition of lipopolysaccharide (LPS 10 mg.L-1) induced a higher level expression of c-myc mRNA within 30 min, maximal expression at 2.5 h and persisted for 6 h. This over-expressing of c-myc mRNA was markedly suppressed by emodin (25 mg.L-1), the inhibition of emodin on c-myc mRNA expression was still seen at 6 h, and the greatest suppressive effect was at 2.5 h. CONCLUSION: Emodin participating in its down-regulatory effect of c-myc mRNA over-expression contributes to its inhibitory action on MC. "